Effect Of Initial Pressure Upon Laminar Burning Velocity Of Methane-AirMixtures (Journal of Engineering, 2010)
The effect of the initial pressure upon the laminar flame speed, for a methane-airmixtures, has been detected paractically, for a wide range of equivalence ratio.In this work, a measurement system is designed in order to measure the laminar flamespeed using a constant volume method with a thermocouples technique. The laminarburning velocity is measured, by using the density ratio method.The comparison of the present work results and the previous ones show goodagreement between them. This indicates that the measurements and the calculationsemployed in the present work are successful and precise.